The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.15376/biores.1.2.248-256
|View full text |Cite
|
Sign up to set email alerts
|

Liquefaction of crop residues for polyol production

Abstract: The liquefaction of crop residues in the presence of ethylene glycol, ethylene carbonate, or polyethylene glycol using sulfuric acid as a catalyst was studied. For all experiments, the liquefaction was conducted at 160 ° C and atmospheric pressure. The mass ratio of feedstock to liquefaction solvents used in all the experiments was 30:100. The results show that the acid catalyzed liquefaction process fit a pseudo-first-order kinetics model. Liquefaction yields of 80, 74, and 60% were obtained in 60 minutes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…Agricultural lignocellulosic residues have been successfully converted into biopolyols using mainly a poly(ethylene glycol) (PEG) and glycerol mix. Application fields for the polymeric products developed from these residues include a wide range of different materials for areas such as packaging and floating 3‐10 …”
Section: Introductionmentioning
confidence: 99%
“…Agricultural lignocellulosic residues have been successfully converted into biopolyols using mainly a poly(ethylene glycol) (PEG) and glycerol mix. Application fields for the polymeric products developed from these residues include a wide range of different materials for areas such as packaging and floating 3‐10 …”
Section: Introductionmentioning
confidence: 99%
“…Biopolyol obtained from the biomass will be a potential alternative of polyester or polyether polyols for making biopolymers. 1,9 Shiraishi et al 10 reported that in the presence of organic solvents like polyethylene glycol and phenols, solid lignocellulosic biomass could be liquefied effectively into liquid products at 120–180°C in the presence of acid catalysts or at 180–250°C without catalysts. Tanaka et al 11 and Harikrishnan et al 12 have used palm oil and castor oil for producing PU foams respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The natural materials like starch, cellulose, soybean oil, 13 sugarcane bagasse, 1 wheat straw, 14 cornstalk 15 and dried distiller grains 16 have been employed for either preparing PUs or modifying their properties and degradability. 9 Kurimoto et al 3 showed that by varying the [NCO]/[OH] ratio, mechanical properties of PU foams can be controlled effectively. Carbon nanotubes (CNTs) have wide variety of applications in nanotechnology, electronics, optics and other fields of materials science due to its high aspect ratio, mechanical strength, electrical and thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Biomass is another example of a raw material used in the plastics industry. The number of reports on the use of various types of the biomass, not only as a source of renewable energy but also as a raw material for receiving, among others, rigid polyurethane foams is constantly increasing [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%